Fiber dissection technique: Lateral aspect of the brain - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
OBJECTIVE: The fiber dissection technique involves peeling away the white matter tracts of the brain to display its three-dimensional anatomic organization. Early anatomists demonstrated many tracts and fasciculi of the brain using this technique. The complexities of the preparation of the brain and the execution of fiber dissection have led to the neglect of this method, particularly since the development of the microtome and histological techniques. Nevertheless, the fiber dissection technique is a very relevant and reliable method for neurosurgeons to study the details of brain anatomic features. METHODS: Twenty previously frozen, formalin-fixed human brains were dissected from the lateral surface to the medial surface, using the operating microscope. Each stage of the process is described. The primary dissection tools were handmade, thin, wooden spatulas with tips of various sizes. RESULTS: We exposed and studied the myelinated fiber bundles of the brain and acquired a comprehensive understanding of their configurations and locations. CONCLUSION: The complex structures of the brain can be more clearly defined and understood when the fiber dissection technique is used. This knowledge can be incorporated into the preoperative planning process and applied to surgical strategies. Fiber dissection is time-consuming and complex, but it greatly adds to our knowledge of brain anatomic features and thus helps improve the quality of microneurosurgery. Because other anatomic techniques fail to provide a true understanding of the complex internal structures of the brain, the reestablishment of fiber dissection of white matter as a standard study method is recommended.
Keywords: fiber dissection technique; microsurgical anatomy; white matter